Neural Mechanisms of Inhibitory Response in a Battlefield Scenario: A Simultaneous fMRI-EEG Study - Ko, Li-Wei; Shih, Yi-Cheng; Chikara, Rupesh Kumar; Chuang, Ya-Ting; Chang, Erik C. (Frontiers in Human Neuroscience, 2016)
The stop-signal paradigm has been widely adopted as a way to parametrically quantify the response inhibition process. To evaluate inhibitory function in realistic environmental settings, the current study compared stop-signal responses in two different scenarios: One uses simple visual symbols as go and stop signals, and the other translates the typical design into a battlefield scenario where a sniper-scope view was the background, a terrorist image was the go signal, a hostage image was the stop signal, and the task instructions were to shoot at terrorists only when hostages were not present but to refrain from shooting if hostages appeared. The battlefield scenario created a threatening environment and allowed the evaluation of how participants’ inhibitory control manifest in this realistic stop-signal task. In order to investigate the participants’ brain activities with both high spatial and temporal resolution, simultaneous functional magnetic resonance imaging (FMRI) and electroencephalography (EEG) recordings were acquired. The results demonstrated that both scenarios induced increased activity in the right inferior frontal gyrus (IFG) and presupplementary motor area (preSMA), which have been linked to response inhibition. Notably, in right temporoparietal junction (rTPJ) we found both higher BOLD activation and synchronization of theta-alpha activities (4-12 Hz) in the battlefield scenario than in the traditional scenario after the stop signal. The higher activation of rTPJ in the battle-field scenario may be related to morality judgments or attentional reorienting. These results provided new insights into the complex brain networks involved in inhibitory control within naturalistic environments.